MPAS-Dev/MPAS-Analysis: v1.2.9 - Xylar Asay-Davis; Milena Veneziani; Phillip J. Wolfram; Luke Van Roekel; Darin Comeau; Riley Brady; stephenprice; gstreletz; Adrian K. Turner; kevin; Mark Petersen; Charles Doutriaux; et al. (Zenodo, 2020)
Minor release. Major Enhancements Add a test suite for MPAS-Analysis on Anvil #741 Minor Enhancements Adds the globally-computed bias mean and rsme values in the title of climatological map plots #739 Break Antarctic melt time series into subtasks per year #747 Add WOA18 and SOSE obs. to time series of ocean regions #748 Various updates to T-S diagrams #749 Reduce the range for melt-rate plots to +/- 20 m/yr #751 Add Rignot obs for Antarctic, FRIS, Ross #752 Move the legend to the lower left for regional profiles #754 Use cartopy coastline by default in polar projection plots #753 Send melt tables to "tables" directory #757 Build region and transect masks from geometric_features aggregation #756 Break hovmollerOceanRegions into its own task #759 Bug fixes A large number fixes revealed by new deprecation warnings #736 Use only one subprocess for MPAS-Tools mask creator #737 Fix masking of ocean regions #740 Switch from matplotlib-base to full matplotlib #745 Fix anvil testsuite #755 Documentation Update tutorial to include HDF5_USE_FILE_LOCKING=FALSE #734 Continuous Integration Fix local package installation directory in Azure #744 Contributors @xylar @milenaveneziani